INTERPRETING SENTENCES OF AN ARTICLE “ISLAM A RELIGION OF PEACE” - Diana Sopha (PHILOLOGY Journal of English Language and Literature, 2021)
This research analyzes meaning interpretation in the sentences of the article entitled “Islam: a Religion of Peace”. This article is analyzed using qualitative descriptive method and semantic theory. This research gives solution for the problems of how to interpret the sentences meaning of the article. This problem can be answered by using semantic theory or the theory of meaning of language. Based on the result of research, the meaning interpretation of the sentences found in the article “Islam: a Religion of Peace” are Islam is a teaching and a religion that believes in God, Prophet Muhammad pbuh. and Qur’an as the holy book. Islam has ideology of peace but there is deviation of the model (teaching of Islam).